2018
DOI: 10.1186/s12936-018-2354-x
|View full text |Cite
|
Sign up to set email alerts
|

Malaria determining risk factors at the household level in two rural villages of mainland Equatorial Guinea

Abstract: BackgroundAfter the introduction of an artemisinin-based combination therapy, the reduction of prevalence of malaria infections has shown a remarkable progress during the last decade. However due to the lack of a consistent malaria control programme and socioeconomic inequalities, Plasmodium infection is still one of the major cause of disease in Equatorial Guinea, namely in the rural communities. This study explored the associated risk factors of malaria transmission at the microeconomic level (households) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 29 publications
2
19
1
1
Order By: Relevance
“…Another fact is that, during hot weather in tropical regions, some individuals do not like to use ITN to protect themselves against mosquito bites. A study conducted by Guerra and colleagues [31] showed that, of the 40% of participants owning ITN in the Guinean village of Miyobo, only 36% ITN users has been consistently using this preventive measure. However, in this study, consistency in ITN use was not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Another fact is that, during hot weather in tropical regions, some individuals do not like to use ITN to protect themselves against mosquito bites. A study conducted by Guerra and colleagues [31] showed that, of the 40% of participants owning ITN in the Guinean village of Miyobo, only 36% ITN users has been consistently using this preventive measure. However, in this study, consistency in ITN use was not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) recommends IPT in pregnancy (IPTp) with sulfadoxine-pyrimethamine (SP) in all areas of Africa with moderate to high malaria transmission. 4,5 In sub-Saharan Africa, 39 countries adopted IPTp between 1993 and 2007. 5 In addition, the concept of IPT has been extended to include infants (IPTi) and children (IPTc; now referred to as SMC (seasonal malaria chemoprevention)).…”
Section: Introductionmentioning
confidence: 99%
“…According to WHO data, malaria causes 15% of all deaths in children under age 5 in Equatorial Guinea. 4 Bioko, an island of Equatorial Guinea off the coast of Cameroon, has historically high malaria transmission. 6 The most recent studies focused on detecting the prevalence of mutations in Pfmdr1 and Pfcrt on Bioko Island.…”
Section: Introductionmentioning
confidence: 99%
“…None of these predisposing factors significantly contribute to the presence of malaria in these neonates. These predisposing factors have been shown to significantly contribute to malaria existence in adults ( Azunie, 2017 ; Essendi et al, 2019 ; Guerra et al, 2018 ; Musoke et al, 2018 ). The passively acquired immunity in the neonates may have been responsible for the protection in this current study.…”
Section: Resultsmentioning
confidence: 99%